PENGEMBANGAN E-LEARNING BERBASIS GOOGLE SITES UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA - Neni Citra Dewi (UNIB Press, 2020)
Thisstudyaimsto: (1)producethedevelopment ofe-learningberbasisgooglesitesimprove student learningachievement (2)describetheeffectivenessof development ofe-learning berbasisgooglesitestoimprovestudentlearningachievement.ThisstudyusesResearch andDevelopmentdesign.Thesubjects ofthis studywerestudents ofgradeXIMultimediaof SMKNegeri 2Rejang Lebong. Data collectiontechniquesusingassessmentsheetsandtests. Dataanalysisusesthe mean (t)andt-test.Theconclusionsofthisstudyare: (1)the devlopment of e-learningberbasisgoogle canimprovestudent achievement,and (2)the development of e-learningberbasis googleeffectivetoincrease learningachievement of studentsof classXI MultimediainAnimasi2D subject